2015
DOI: 10.1186/s12931-015-0221-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular trap (NET) formation characterises stable and exacerbated COPD and correlates with airflow limitation

Abstract: BackgroundCOPD is a progressive disease of the airways that is characterized by neutrophilic inflammation, a condition known to promote the excessive formation of neutrophil extracellular traps (NETs). The presence of large amounts of NETs has recently been demonstrated for a variety of inflammatory lung diseases including cystic fibrosis, asthma and exacerbated COPD.ObjectiveWe test whether excessive NET generation is restricted to exacerbation of COPD or whether it also occurs during stable periods of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(146 citation statements)
references
References 70 publications
8
124
0
1
Order By: Relevance
“…As noted, histones are major components of neutrophil NETs. NETs are found to contribute to adverse inflammatory responses in auto-immune diseases such as systemic lupus erythematosus [81][82][83] or respiratory impairment in cystic fibrosis [61,84,85] or chronic obstructive pulmonary disease [86]. Some studies have histones of 50 μg/ml or more have been found to induce death of endothelial and lung epithelial cells [87].…”
Section: Histones As Inducers Of Inflammation and Thrombosismentioning
confidence: 99%
“…As noted, histones are major components of neutrophil NETs. NETs are found to contribute to adverse inflammatory responses in auto-immune diseases such as systemic lupus erythematosus [81][82][83] or respiratory impairment in cystic fibrosis [61,84,85] or chronic obstructive pulmonary disease [86]. Some studies have histones of 50 μg/ml or more have been found to induce death of endothelial and lung epithelial cells [87].…”
Section: Histones As Inducers Of Inflammation and Thrombosismentioning
confidence: 99%
“…As mentioned above in this review, NETs are associated with inflammation and disease severity in chronic airway diseases [34,35] . While glucocorticoid had no effect on the NETs formation in peripheral blood neutrophils induced by activation, phorbol myristate acetate (PMA), in vitro [107] .…”
Section: Other Factorsmentioning
confidence: 76%
“…NETs are an important component of innate immunity, but their role is ambiguous as causing severe host tissue damage in certain pathological conditions [33] . Accumulating evidences shown that NETs directly contributed to host cell death and chronic tissue damage when formed in excess or were insufficiently cleared by mechanisms that were still poorly understood [34] . Recently, several studies have detected increased NETs and NET components in neutrophils from airways or peripheral blood of patients with asthma, suggesting an involvement of NETs in asthma pathogenesis [35][36][37] .…”
Section: Reviewmentioning
confidence: 99%
“…Published applications of the package npmv can be found, for example, in Nardone et al (2014Nardone et al ( , 2015, and Grabcanovic-Musija et al (2015).…”
Section: Global Multivariate Test Statisticsmentioning
confidence: 99%